Forced Convection inside a Vertical Circular Cylinder with an Inner Coaxial Rectangular Cylinder - Boukhari, Ali; Boughezala, Hamad Ahmed; Bouabdallah, Said (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2021)
In this work, we performed a numerical simulation of laminar forced convection and, in an annular space inside a vertical circular cylinder with an inner coaxial rectangular cylinder having an aspect ratio (height/radius) γ=2, filled with a liquid metal (Pr = 0.0023). Six annular gaps R =0.9, 0.8, 0.7, 0.6, 0.5 and 0.4 were studied. The governing equations are solved using the ANSYS Fluent code which is based on the finite volume method. SIMPLE algorithm is employed for the pressure-velocity coupled momentum equations. Two cases of the rotating parts of the cylinders are investigated and the effect of Reynolds number on the flow are examined. The obtained results of the forced convection show that the increase of the Reynolds number Re affects straightly on the structure of the flow wherever the velocity field are destabilized and the strongest stabilization of the velocity field occurs when the flow generated by the rotating of the circular cylinder and the rectangular cylinder.Keywords: forced convection, annular gap, circular cylinder, rectangular cylinder, co-rotating.